Pembelajaran Dengan Metode Diskusi Kelas - Nurul Afifah (Tarbawiyah Jurnal Ilmiah Pendidikan, 2014)
In the democratic education today , the method of discussion gets considerable attention because it is more importance in stimulate the students to think and express opinions and ideas freely and independently. Discussion method is a method of teaching that is closely associated with learning to solve problems . Application students were given the task to solve a problem by working with the group , or discussed together. Objectives to be achieved in the method of discussion include: the student can think democratically, can appreciate the difference, to train students to think with deep reflection, and train them to be responsible for his opinion. The variety discussion models are: a whole group, buzz groups, panels, syndicate groups, brainstorming groups, symposia, colloqium, informal debate and fish bowl . All of discussion models is hope give the learning to the students that many alternatives to solving the problems. Perhaps from the others opinions can be found the best solution to solve the problems.